Pengembangan Mindset Guru Kelas Dalam Pemberdayaan Pendidikan Karakter Siswa SD Negeri 133 Kelurahan Talang Bakung Kecamatan Paal Merah Lama Kota Jambi - Yudha, Redi Indra (Universitas Batanghari Jambi, 2022)
This study aims to develop an open and creative way of thinking, as a representation that emphasizes divergent rather than convergent thinking patterns, has a high sensitivity to problems in associative, elaborative thinking in turn to be able to improve the teacher's ability to make new combinations in a learning process. which was held at SD Negeri 133 Jambi City. This research design uses descriptive qualitative. Meanwhile, the technique in this study uses a purposive technique, namely the determination of informants is not based on guidelines or based on population representation, but based on the depth of information needed related to the research problem. The results showed that: 1) Teachers were still focused on the related curriculum due to the time and hours of study, as well as maintaining learning outcomes, 2) Empowering students' character tended to maintain academic achievement and school policies.